1868 Or. Gen. Laws 18-19, An Act to Protect the Owners of Firearms, §§ 1-2. - (:unkn) unknown (General Publisher, 1868)
Every white male citizen of this state above the age of sixteen years, shall be entitled to have, hold, and keep, for his own use and defense, the following firearms, to wit: either or any one of the following-named guns, and one revolving pistol: a rifle, shot-gun (double or single barrel), yager, or musket; the same to be exempt from execution, in all cases, under the laws of Oregon. § 2. No officer, civil or military, or other person, shall take from or demand of the owner any fire-arms mentioned in this act, except where the services of the owner are also required to keep the peace or defend the state.
--
Keywords: GUARANTEED RIGHT